BALAI LATIHAN KERJA (BLK) DALAM MENINGKATKAN CIVIC COMPETENCE TENAGA KERJA DI ERA REVOLUSI 4.0 - Ammar Zaki; Akhyar Akhyar; Saifuddin Saifuddin; Muhammad Halimi; Al furqan Al Furqan (Jurnal Dedikasi Pendidikan, 2023)
This article aims to explain the increase of civic competence for the workforce in vocational training centers (BLK) in the era of the industrial revolution 4.0. This research uses a qualitative descriptive method. This research was conducted at BLK level 1 UPTP Aceh. Sources of data obtained by observation, interviews, and document analysis. Data analysis uses mile and hubberman by data reduction, triangulation and display. The results of the study show that BLK have carried out civic competence improvements through soft skill and hard skill training programs and adapted to the 4.0 industrial revolution era. This can be seen through the determination of programs that use TNA (training need analysis), its means looking at programs by  developments needs of the labor market before opening the type of training programs and based on DUDI (business and industry).